Interactions between islet-resident macrophages and β cells in diabetes - Zhang, Danhuai; Meng, Lingzhe; Xi, Minghui; Li, Shuai; Chen, Wantong; Li, LuYi; Dong, Lingling; Wu, Na (Frontiers in Immunology, 2025)
In diabetes, islet-resident macrophages (IRMs) and β cells engage in multifaceted interactions through diverse signaling pathways and cell–cell contact within the islet microenvironment, jointly shaping both homeostasis and disease progression. This review first outlines the origin, renewal dynamics, and phenotypic heterogeneity of IRMs, highlighting their essential roles in maintaining metabolic and immunological homeostasis under physiological conditions. We then emphasize the dual role of IRMs in type 1 and type 2 diabetes (T1DM and T2DM): in T1DM, they drive autoimmunity via antigen presentation and pro-inflammatory cytokine secretion; in T2DM, metabolic stress induces M1 polarization, exacerbating β cell dysfunction and dedifferentiation. We further explore molecular mechanisms modulating IRM–β cell crosstalk, including neuro-immune-endocrine networks (e.g., α1-adrenergic signaling), Interleukin-1 Beta (IL-1β) feedback loops, and the C-X-C Motif Chemokine Ligand 16 (CXCL16)/Oxidized Low-Density Lipoprotein (OxLDL) axis. The paracrine actions of growth factors such as PDGF, VEGF-A, and IGF-1 in β cell proliferation and regeneration are also reviewed. Additionally, novel therapeutic targets, such as G Protein-Coupled Receptor 132 (GPR132) and exosomal miRNAs, offer promising strategies to precisely regulate macrophage polarization and protect β cells. Finally, we discuss the application of advanced technologies—such as single-cell sequencing and intravital imaging—in deciphering dynamic IRM–β cell interactions and highlight the prospects of modulating islet macrophage phenotypes to restore metabolic and immune balance in future research and clinical translation.